Feminist Shadow Networks: 'Thinking, Talking, and Making' as Praxes of Relationality and Care - Aynur Kadir; Brianna Ivy Wiens; Shana Danielle MacDonald (Digital Studies, 2023)
In the face of the constraints and pressures of the neoliberal university, this article argues for the importance of feminist shadow networks as a response to the unequal academic grounds on which scholars and students are asked to situate themselves. Calling for such networks as a model of relationality, we suggest that critical friendship and careful support are necessary for addressing the exacerbated correlating class-, race-, and gender-based inequities that continue to haunt us. We outline three praxes of “think, talk, and make” that we, the Feminist Think Tank, a research-creation collective that advances work on feminist media, art, and design, rely on in our feminist shadow work. In the section on THINKING, we offer the guiding orientations to our work that are grounded in epistemologies of un-learning, feminist relationality, and critical friendship. Next, in TALKING, we discuss our approaches to collaboration, analysis, and community, which are nested within epistemologies of careful support and trust. Last, in MAKING, we outline recent projects that Feminist Think Tank has undertaken, offering examples of how we create our own digital feminist interventions from the space of the feminist shadow network. Overall, this work contributes to more careful and critical approaches to research, data, technological affordances, and feminist histories via our feminist shadow networks, offering alternative stories and ways of being in the academy.Face aux contraintes et aux pressions de l'université néolibérale, cet article défend l'importance des réseaux fantômes féministes comme réponse aux inégalités académiques sur lesquelles les chercheurs et les étudiants sont invités à se situer. En appelant à de tels réseaux comme modèle de relationnalité, nous suggérons qu'une amitié critique et un soutien attentif sont nécessaires pour aborder les inégalités exacerbées et corrélées basées sur la classe, la race et le genre qui continuent à nous hanter. Nous décrivons trois pratiques de "penser, parler et faire" sur lesquelles nous, The Feminist Think Tank, un collectif de recherche-création qui fait avancer le travail sur les médias, l'art et le design féministes, nous appuyons dans notre travail de l'ombre féministe. Dans la section PENSER, nous présentons les orientations qui guident notre travail et qui sont fondées sur les épistémologies du désapprentissage, de la relationnalité féministe et de l'amitié critique. Ensuite, dans la section PARLER, nous discutons de nos approches de la collaboration, de l'analyse et de la communauté, qui s'inscrivent dans des épistémologies de soutien attentif et de confiance. Enfin, dans MAKING, nous décrivons les projets récents entrepris par The Feminist Think Tank, en offrant des exemples de la manière dont nous créons nos propres interventions féministes numériques à partir de l'espace du réseau fantôme féministe. Dans l'ensemble, ce travail contribue à des approches plus prudentes et critiques de la recherche, des données, des possibilités technologiques et des histoires féministes par le biais de nos réseaux fantômes féministes, offrant des histoires et des manières alternatives d'être dans le monde académique.